2021
DOI: 10.1097/icu.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of ultrasound in cataract surgery

Abstract: Purpose of reviewModern phacoemulsification machines apply ultrasound through a variety of settings and parameters to remove a cataract. Using these new technologies efficiently is critical for both reducing surgical times and improving postoperative outcomes. The present article reviews recent findings in phacodynamics to explore the optimum use of ultrasound in cataract surgery. Recent findingsIn studies seeking to determine the optimum parameters in both fluidics and power, increased power and aspiration do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Preoperatively, the ocular indexes of the two groups of patients were compared (P > 0.05), and at 6 weeks postoperatively and 12 weeks postoperatively, the naked-eye visual acuity, BCVA, and anterior chamber depth of the patients in the observation group were better than those of the control group (P < 0.05), and the intraocular pressures of the patients in the two groups were compared (P > 0.05), as shown in Table 2. Preoperatively, the CECs, central corneal thickness, and ocular surface disease index were compared between the two groups (P > 0.05), and at 6 weeks postoperatively and 12 weeks postoperatively, the CECs, central corneal thickness, and ocular surface disease index of patients in the observation group were superior to those of the control group (P < 0.05), as shown in Table 3 [18].…”
Section: Comparison Of Ocular Indices Before and After Surgerymentioning
confidence: 97%
“…Preoperatively, the ocular indexes of the two groups of patients were compared (P > 0.05), and at 6 weeks postoperatively and 12 weeks postoperatively, the naked-eye visual acuity, BCVA, and anterior chamber depth of the patients in the observation group were better than those of the control group (P < 0.05), and the intraocular pressures of the patients in the two groups were compared (P > 0.05), as shown in Table 2. Preoperatively, the CECs, central corneal thickness, and ocular surface disease index were compared between the two groups (P > 0.05), and at 6 weeks postoperatively and 12 weeks postoperatively, the CECs, central corneal thickness, and ocular surface disease index of patients in the observation group were superior to those of the control group (P < 0.05), as shown in Table 3 [18].…”
Section: Comparison Of Ocular Indices Before and After Surgerymentioning
confidence: 97%
“…Phacoemulsification machines have evolved to include a torsional ultrasound delivery system or femtosecond laser to deliver ultrasound energy efficiently or decrease the total ultrasound energy [13][14][15]. Another recent advancement has been the switch to dual-linear foot-pedal control (Stellaris Elite ® , Bausch+Lomb, St. Louis, MO, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The application of femtosecond laser-assisted cataract surgery (FLACS) provides precise, clear corneal incisions (CCIs), accurate anterior capsulotomy, efficient nuclear fragmentation and reduction of corneal endothelial cell loss. [1][2][3] This technique has the potential to improve surgical outcomes and enable inexperienced surgeons to perform more predictable and reproducible cataract surgery. [4][5][6] Several studies have shown the notable benefits of this technology, including the increased precision of anterior capsulotomies, less intraocular lens (IOL) tilt and decentration, and substantial reductions in ultrasound power and effective phacoemulsification time (EPT).…”
Section: Introductionmentioning
confidence: 99%